Impact of cardiopulmonary bypass and surgical complexity on plasma soluble urokinase-type plasminogen activator receptor levels after cardiac surgery. (1st December 2021) - Dardashti, Alain; Sterner, Niklas; Fisher, Jane; Thelaus, Louise; Nilsson, Johan; Linder, Adam; Zindovic, Igor
Abstract: Background: Circulating soluble urokinase plasminogen activator receptor (suPAR) is a marker of inflammation with prognostic value for elevated risk of morbidity and mortality. It has not yet been shown how the inflammatory process induced by cardiac surgery affects suPAR concentrations postoperatively Methods: In a prospective observational study, plasma suPAR levels were measured in 30 patients undergoing cardiac surgery with cardiopulmonary bypass (CPB), pre-, peri, post-operatively, and 3–5 days after surgery. Fifteen patients underwent coronary artery bypass grafting (CABG) and 15 underwent complex procedures with longer CPB duration. Concentrations of suPAR at each time point were compared to the preoperative levels and compared between the two groups. Results: In both groups, plasma suPAR concentrations were significantly higher on the first postoperative day (3.27 (interquartile range (IQR) 2.75–3.86) µg/L compared to baseline (2.62 (1.98–3.86)) µg/L, p < .001. There were no significant differences in suPAR concentrations between the groups at any time point. Preoperatively, the median suPAR concentration was 2.57 (2.01–3.60) µg/L in the CABG group versus 2.67 (1.89–3.97) µg/L in the complex group ( p = .567). At ICU arrival 2.48 (2.34–3.23) µg/L versus 2.73 (2.28–3.44) µg/L in CABG and complex patients, respectively ( p = .914). There was no difference in suPAR concentrations between the groups on postoperative day 1 (3.34 (2.89–3.89) versus 3.19 (2.57–3.62) p = .967) or 3–5 days after surgery (2.72 (1.98–3.16) versus 2.96 (2.39–4.28) p = .085. Conclusions: After a transient rise on the first postoperative day, the suPAR levels returned to the preoperative levels by the third postoperative day. There was no significant difference in suPAR levels between the routine CABG and complex group with longer CPB time.